EVALUATION OF INHIBITORY AND TOXICITY EFFECTS OF XYLOPIA AETHIOPICA FRUIT EXTRACT AGAINST ESBL-PRODUCING BACTERIAL STRAINS - Musbau, S.; Asiru, R. A.; Odewade, J. O. (FUDMA Journal of Sciences, 2024)
This study investigated the inhibitory and toxicity effects of Xylopia aethiopica, widely utilized in traditional medicine, particularly in Nigeria and West Africa. The clinical isolates obtained from Department of Pathology, Federal Medical Center in Nguru, Yobe State which includes Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa, Shigella boydii and Klebsiella oxytoca were identified and confirmed to produce Extended-Spectrum Beta-Lactamase (ESBL) through standard microbiological methods, followed by genotyping via conventional Polymerase Chain Reaction (PCR). The bioactivity of Xylopia aethiopica fruit extract against Extended-Spectrum Beta-Lactamase producing bacterial isolates was evaluated using the agar well diffusion method. The quantitative phytochemical analysis carried out through Soxhlet extraction revealed a range of bioactive compounds in varying amounts such as flavonoids, tannins, phenols, saponins and steroids, while alkaloids were not detected in the chloroform extract. Both ethanol and chloroform extracts displayed significant antibacterial activity, with inhibition zones of 27.50 mm at 100% concentration, surpassing the reference drug, Amikacin (18.03 mm). Additionally, in vitro toxicity assessment indicated an LD50 of 3,807.9 mg/kg, indicating a slight toxicity level. These findings suggest that Xylopia aethiopica not only has promising antibacterial properties against ESBL-producing bacteria but also warrants caution due to its potential toxicity. The study emphasizes the need for careful consideration when incorporating Xylopia aethiopica into medicinal practices.